TouchPivot: Blending WIMP & Post-WIMP Interfaces for Data Exploration on Tablet Devices - Jo, Jaemin; L’Yi, Sehi; Lee, Bongshin; Seo, Jinwook (2017 ACM Conference on Human Factors in Computing Systems (CHI), 2017)
Recent advancements in tablet technology pose a great opportunity for information visualization to expand its horizons beyond desktops. In this paper, we present TouchPivot, a novel interface that assists visual data exploration on tablet devices. With novices in mind, TouchPivot supports data transformations, such as pivoting and filtering, with simple pen and touch interactions, and facilitates understanding of the transformations through tight coupling between a data table and visualization. We bring in WIMP interfaces to TouchPivot, leveraging their familiarity and accessibility to novices. We report on a user study conducted to compare TouchPivot with two commercial interfaces, Tableau and Microsoft Excel’s PivotTable. Our results show that novices not only answered data-driven questions faster, but also created a larger number of meaningful charts during freeform exploration with TouchPivot than others. Finally, we discuss the main hurdles novices encountered during our study and possible remedies for them.